Penggunaan Semen Tipe Portland Pozzolan Cement (PPC) Pada Beton Roller Compacted Concrete (RCC) Terhadap Kuat Tekan Ditinjau dari Durabilitasnya - Mbani, Umbu Valentino Kanna Ngundju; Sulistyorini, Dewi; Gutama, Detha Sekar Langit Wahyu; Ela, Alfredo Yogusta Figo; Saputro, Agung Purwo Saputro (RENOVASI : Rekayasa Dan Inovasi Teknik Sipil, 2025)
Roller Compacted Concrete (RCC) is a construction material frequently used in massive infrastructure projects such as dams, embankments, highways, and airport runways. This concrete is characterized by a special casting method involving the use of a roller compactor, which produces a dense and strong concrete structure at a relatively low cost. The research materials used are portland pozzolanic cement (PPC), coarse aggregate with a maximum size of 19, fine aggregate, a ratio of water and mineral superplasticizer additives of 0.5%. The manufacture of cylindrical test specimens measuring 150 x 300 mm in accordance with ASTM C1435 which were compacted using a vibrator hammer. The purpose of this study was to determine the compressive strength of RCC concrete with PPC cement material and the modulus of elasticity of concrete with ordinary water immersion treatment and sodium sulfate at the age of 14 days and 28 days. The average compressive strength test results for RCC concrete using PPC cement showed the highest result in the sodium sulfate immersion treatment at 28 days at 43.65 MPa and the lowest result with ordinary water immersion treatment at 28 days at 34.35 MPa.